2022
DOI: 10.3390/cancers14122827
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC Alteration Contributes to Tumor Growth and Immune Escape in Pan-Cancer

Abstract: The accumulating evidence demonstrates that the apolipoprotein B mRNA editing enzyme catalytic polypeptide-like (APOBEC), DNA-editing protein plays an important role in the molecular pathogenesis of cancer. In particular, the APOBEC3 family was shown to induce tumor mutations by an aberrant DNA editing mechanism. However, knowledge regarding the reconstitution of the APOBEC family genes across cancer types is still lacking. Here, we systematically analyzed the molecular alterations, immuno-oncological features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Studies revealed other molecular markers that could be predictive of the efficacy of immunotherapy in advanced NSCLC. For example, detected through next-generation sequencing, the apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like, also known as APOBEC, has been reported to predict the efficacy of immunotherapy ( 70 ), not only in NSCLC but also in pan-cancer analysis ( 71 ). Previous study ( 72 ) found that APOBEC signature in metastatic NSCLC is strongly associated with better immune responses, in terms of ORR and PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed other molecular markers that could be predictive of the efficacy of immunotherapy in advanced NSCLC. For example, detected through next-generation sequencing, the apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like, also known as APOBEC, has been reported to predict the efficacy of immunotherapy ( 70 ), not only in NSCLC but also in pan-cancer analysis ( 71 ). Previous study ( 72 ) found that APOBEC signature in metastatic NSCLC is strongly associated with better immune responses, in terms of ORR and PFS.…”
Section: Discussionmentioning
confidence: 99%
“…APOBEC3s can also impact tumor growth through non-mutagenic pathways that shape the tumor immune microenvironment (Table 4 ). APOBEC3s are immunosuppressive in some cancers, and higher APOBEC3B expression has been associated with less immune cell infiltration in adrenocortical carcinoma and gastric cancer [ 37 , 162 ]. APOBEC3 expression has also been associated with greater infiltration of immunosuppressive mediators such as myeloid-derived suppressor cells (MDSCs) and tumor-associated macrophages (TAMs) in a mouse model of hepatocellular carcinoma [ 163 ].…”
Section: Impact Of Apobec3s Through Mutagenic and Non-mutagenic Pathwaysmentioning
confidence: 99%
“…Fewer MDSCs and naïve CD4+ T cells Patient [ 160 ] 3B Activating More cytotoxic T-cells with a higher CD8+/CD3+ ratio Patient [ 35 ] Glioma 3B, 3C, 3D, 3F, 3G, 3H Activating Increased myeloid cell infiltration, IFN-γ signaling, and PD-L1/2 expression Patient [ 51 ] Lung 3B Activating More activated CD4+ T cells, CD8+ T cells, and NK cells. Fewer regulatory T cells Patient [ 166 ] 3B Activating Upregulation of immune genes and more T cell infiltration to the tumor site Patient [ 36 ] Mutation burden Activating Enrichment of interferon pathways Patient [ 89 ] Melanoma 3B Activating Immune activation in a multi-cancer analysis Patient [ 162 ] Ovarian 3B Activating Greater tumor immune cell infiltration Patient [ 41 ] 3G Activating Higher immune cell counts in the tumor microenvironment Patient [ 167 ...…”
Section: Impact Of Apobec3s Through Mutagenic and Non-mutagenic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity leaves signatures along the double helix that are clearly traceable to A3 family members and are found predominantly in cancer cells [73]. As the structural details of A3s interaction with nucleic acids are being unveiled [74], the ambivalent effect of these protective enzymes is also being highlighted, as an elevated expression of APOBEC3s may provide a reason for aberrant cancer-inducing somatic mutations in human papilloma virus (HPV) [75][76][77] and HBV [78] infections, as well as an extensive range of other tumor types [73,79,80], even in the context of inflammation [81].…”
Section: Overview Of Apobec3 Functionsmentioning
confidence: 99%